Impact of Homestead Agro-Forestry on Sustaining Livelihoods of Rural Poor in Mymensingh District of Bangladesh - Jahan, N; Rashid, MHA; Jinan, T; Islam, S (Progressive Agriculture, 2013)
This study determines the impact of homestead agro-forestry on livelihood of rural households in Mymensingh district. In total 100 homestead agro-forestry practicing farmers from three upazilas namely Mymensingh Sadar, Bhaluka and Muktagachha of Mymensingh district were randomly selected for this study following a purposive sampling technique. Analysis was done considering the pre (before) and post (after) homestead agro-forestry practicing condition of farmers. The major findings of the study showed that per hectare net returns for vegetables and fruits cultivation were Tk. 6,703.62 and Tk. 14,532.61 respectively considering all farms. On an average, the contribution of vegetables and fruits in total homestead income was 20.23 per cent in before and 22.46 per cent in the after homestead agro-forestry practicing situation indicating enough potentiality to generate income from homestead agro-forestry. It was found that vegetables cultivation was much better for small farmers compared to medium and large farmers. For fruits and vegetables enterprises, the performance of large farmers was better than small and medium farmers. Large farmers were more efficient than medium and small category in case of fruit production. Most of the variables included in the Cobb-Douglas production function model had significant impact on homestead agro-forestry. The study revealed that homestead agro-forestry had positive impact on improving the status of rural households and women empowerment. DOI: http://dx.doi.org/10.3329/pa.v19i1.17367 Progress. Agric. 19(1): 169 - 178, 2008